Support for patients and radiological image receivers in patellar X-ray examinations - Costa, Rita Zanlorensi Visneck (2023)
Objectives: Develop two supports to assist in performing knee exams, in which acquisitions of axial radiographic images of the patella are required. Materials and methods: The prototypes were built and tested based on anthropometric measurements collected from volunteer patients, and measurements from the X-ray equipment at the Radiology Laboratory of UTFPR (Brazil). One support had the function of accommodating the knees and the other the image receptors. Results and discussions: The materials selected for making the prototypes are low-cost and easily accessible. In preliminary evaluations, the prototypes proved to be resistant to handling. The tests with the two supports met the ergonomic parameters of the volunteer patients. The support for accommodation of the patients' knees had good results in the testing phase, but when used in examinations of different patients, it was verified that it needed to be adjusted according to the anatomy of each one, so it was not used. The support for the image receptor, on the other hand, presented satisfactory results, both for the patients and for the professionals of radiological techniques. This streamlined the exam routine, provided comfort to the patient, and the acquired images presented good diagnostic quality. In future work, it is intended to develop other knee supports for a greater diversity of anatomical shapes.